A study of shipping operation and procedure in MISC agencies (Port Klang) / Shahrum Ibrahim - Ibrahim, Shahrum (2001)
There is two purpose of this research, firstly, is to to examine the shipping operation and procedures in MISC ( /Agencies ), Port Kelang. Second, is to study the problems that exist. In this study, data were collected from Primary and Secondary Data. Primary Data is from MISC ( Agencies ) and the Secondary is from Reference Books, articles, journals and brochures. The shipping operation and procedures is important. It is including the location of Port Kelang, labour and equipment and also the Shipping operation and procedures itself. The research is also to study the problems in Port Authority and MISC ( Agencies ) itself.